Two new species of Orgilus Haliday from the Russian Far East (Hymenoptera, Braconidae). Contributions to the knowledge of East Palaearctic insects (9). - Belokobylskij, Sergej A.; Taeger, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 1998)
Orgilus fulvus sp. n. and Orgilus chankaicus sp. n. are described from the Russian Far East. Keywords Orgilus, Hymenoptera, Braconidae, new species, Russian Far East, East Palaearctic. Nomenclatural Acts chankaicus Belokobylskij & Taeger, 1998 (Orgilus), spec. n. fulvus Belokobylskij & Taeger, 1998 (Orgilus), spec. n.